La musicografía braille como recurso didáctico para docentes de lectura musical del nivel inicial del conservatorio Salvador Bustamante Celi de Loja período 2013-2014 - Arevalo Arevalo, Jorge Antonio (2014)
In the process of research entitled "MUSICOGRAPHY BRAILLE AS EDUCATIONAL RESOURCE FOR TEACHERS OF READING INITIAL LEVEL MUSIC CONSERVATORY OF SALVADOR BUSTAMANTE CELI Loja PERIOD 2013-2014 , was raised as main objective to contribute to the knowledge of Braille Musicography as a teaching resource in the initial level of the Conservatory. To obtain technical data of the survey of teachers of music reading and blind persons registered in the Municipal Speaker Loja Braille library was used. The research process was performed by using the scientific method, the analytical method and deductive - inductive. The analysis and interpretation of results information set forth in tabular and graphical form, obtained by applying various research tools among stakeholders. The main conclusion of this research is posed as: The lack of music teachers trained in the use of the International Manual of Braille Musicography and appropriate teaching materials, has caused a large number of blind musicians do not know this system and performers are heard . The main recommendation that arises is: Include a cross-cutting policy and institutional Conservatory Curriculum Plan, the use of Braille Musicography to cover future demand for blind students from the city of Loja. Similarly alternative guidelines that constitute the research proposal, consisting of the elements of training in Braille and teachers taught the initial level Conservatorio which the functionality of this system was demonstrated which is based Musicography arise methodological Manual on the International Braille Musicography essential for the musical education of blind students including teaching resource .